Design Thinking in Education: Evaluating the Impact on Student Entrepreneurship Competencies - Lia Alexandra Baltador; Valentin Grecu; Nancy Diana Panța; Anabella Maria Beju (Education Sciences)
This study investigates the effectiveness of the Sibiu Impact Makers program, a 14-week social entrepreneurship initiative at Lucian Blaga University of Sibiu, which integrates Design Thinking to develop entrepreneurial competencies among students from the faculties of Economic Sciences, Engineering, as well as Social Sciences and Humanities. Using a quasi-experimental design, the study employed a pre-and-post-analysis based on the EntreComp Framework to assess changes in entrepreneurial competencies, revealing significant post-program improvements. To situate this research within the broader academic landscape, a bibliometric analysis was conducted to identify trends linking Design Thinking and entrepreneurial education. The findings indicate that the program enhances entrepreneurial skills, with impact variations tied to students’ learning styles, as classified by the Honey and Mumford Learning Style Questionnaire. However, as a case study with a sample size of 58, findings may have limited generalizability. This research contributes to the discourse on personalized and experiential education, suggesting that integrating Design Thinking with tailored learning strategies can play a vital role in entrepreneurship education.